The Long and the Short of It: The Influence of Briefs on Outcomes in the Roberts Court - Morgan L.W. Hazelton; Rachael K. Hinkle; James F. Spriggs (Washington University Journal of Law & Policy, 2017)
This Article considers the role of information, affected groups, and persuasion in the connection between justice votes and the content of briefs in the Roberts Court. Hazelton, Hinkle, and Spriggs shed new light on the previously observed finding that the side with the most briefs is more likely to win. The authors find that the true advantage lies in providing the Court with a greater amount of information overall, and that holding total information constant, a greater number of briefs is, surprisingly, a disadvantage.
Keywords: Roberts Court; Supreme Court; Briefs; Influence; Success; Information; Groups; Persuasion